Efficacy of Selective Laser Trabeculoplasty vs Eye Drops as a First Line Treatment of Primary Open Angle Glaucoma - Neeharika Shah; Jinal Makwana; Sanket Oza; Nilam Makwana (Delhi Journal of Ophthalmology)
Purpose: Selective laser trabeculoplasty (SLT) is a quick, outpatient procedure with minimal recovery time and a good safety profile. However, the role of laser trabeculoplasty in the treatment of glaucoma is still not well defined. This study is done to compare the effectiveness of selective laser trabeculoplasty as a first line treatment of Primary Open Angle Glaucoma (POAG) against conventional medical treatment with eye drops. Methods: A prospective comparative study was performed at a tertiary care centre in western India from October 2019 to October 2021. Study included 64 patients of mild to moderate severity newly diagnosed open angle glaucoma randomly given SLT or medical treatment as a first line treatment and followed up on 1st week,1st month,3rd month,6th month and 1 year to determine whether laser treatment; Achieves the desired level of intra-ocular pressure (IOP) in comparison to topical antiglaucoma medications, leads to non-progression of visual field during course of treatment, achieves equivalent levels of visual function after 1 year, is well or better tolerated by patients, needs any adjuvant treatment during course of treatment, costs less than the conventional treatment pathway of antiglaucoma medications or not. Results: In both study groups (treatment with SLT and treatment with eyedrops) we did not observe significant differences in Shaffer grading of angle width on gonioscopy, in cup-disc ratio, in visual field examination and pachymetry after 1 year of follow up but IOP was significantly decreased with increasing follow up. Only one patient needed repeat SLT and no patient of SLT group needed any adjuvant treatment. In eyedrops group pre-treatment mean IOP value was 19.125 and that of SLT group was 19.66, and at the end of follow-up in eyedrops group mean IOP value was 15.47 and in SLT group it was 15.84. So, in both groups of study IOP decreased significantly. We observed similar decrease of IOP between two groups (P-value 0.2703) from pre-treatment to post-treatment. Conclusion: SLT is possibly as effective as topical anti glaucoma medications in the treatment of patients with primary open angle glaucoma.